Policy Strategy to Accelerate Digitalization in the era of revolution 5.0 in developing countries - Isra Muksin; Mansyur Djamal; Ardiyanto Saleh Modjo; Nurwita (PT. Anagata Sembagi Education, 2024)
The rapid advancement of technology in the era of Industry 5.0 necessitates accelerated digitalization in developing countries to enhance economic growth, improve competitiveness, and reduce socio-economic disparities. This study employs a quantitative research method, utilizing survey data collected from 230 respondents representing diverse sectors, including government, private enterprises, and educational institutions. The primary objective is to assess the effectiveness of policy strategies in fostering digital transformation, with a focus on identifying key drivers and barriers. The results emphasize the critical role of robust digital infrastructure, targeted government incentives, and active engagement in public-private partnerships. Additionally, the study highlights the significance of digital literacy programs in bridging skill gaps and promoting innovation. Findings suggest that countries prioritizing comprehensive digital policies, workforce upskilling, and inclusive technology adoption demonstrate marked progress in their digitalization efforts. This paper concludes by recommending the implementation of adaptive regulatory frameworks, increased investments in emerging technologies, and strengthened collaboration across sectors to drive long-term, sustainable digital growth and development in the context of Industry 5.0.